Tingkat Keberhasilan Tendangan Penalti Menggunakan Kaki Bagian Dalam Dan Punggung Kaki Dimasa Pandemi Covid-19 - Hasmarita, Sony; Abdul Rohman, Agus; Ishak, Muchamad (STKIP Pasundan, 2022)
This study aims to determine the success rate of penalty kicks using the inner leg and instep. The research method used is experimentation, with a design using the One Group Pretest Post Test design. The population is students of SMAN 1 Padalarang, futsal extracurricular members totaling 20 people. Sampling uses total sampling, so the sample is 20 people. The instrument used a penalty test with the instep and inner leg. There are significant results from the initial test results of penalty kicks using the instep 70% of students are in the category of less once while the other 30% of students are in the less category, the final test of penalty kicks using the instep of 70% of students is in the less category while 30% of other students are in the sufficient category can be seen there is an increase in penalty kicks using insteps